Approach of the systems to problem of individualization of training of fighters - Latyshev, S. V. (Physical Education of Students, 2013)
Purpose of work - to develop the system of individualization of the stage-by-stage training in a free fight. The system is directed on an exposure, forming, development and perfection of own style of opposing. The synthesized system includes managing (trainer) and guided (sportsman) subsystems. For the system is certain external environment from two blocks: rules of competitions and scientific knowledge. These 2 blocks suffice full determine the conduct of the system. Set and described intercommunication between managing and guided subsystems; between an external environment and all of system of individualization of the stage-by-stage training. It is show that a trainer sets the managing affecting sportsman to on to three to directions: block of training activity; block of competition activity; block of extra training and extra competitive activity. It is marked that the last updates of rules of competitions produced new, more hard requirements to the level of development of the special endurance.